2018
DOI: 10.1166/asl.2018.12517
|View full text |Cite
|
Sign up to set email alerts
|

Architectural History Education: Students’ Perception on Mobile Augmented Reality Learning Experience

Abstract: Web of Science [v.5.32]-Web of Science Core Collection Full Record apps.webofknowledge.com.ezproxy.um.edu.my/full_record.do?product=WOS&search_mode=GeneralSearch&qid=3&SID=C2cNDkkes4dPbeiXqmt&p… 1/2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…The main finding had to do with the didactic potential to the learning experience by integrating AR and its development by the students. Finally, the work of Sanusi et al (2018) carried out through mobile devices and focusing in the learning of content for the class History of Architecture, confirmed the findings of other research that used AR in the classroom and concluded that its use with mobile devices benefited the flexible and intuitive learning of the students. Lastly, Villota and Vasconez (2020) conducted first-hand experimentation when they develop an AR app for first aid training named First Aid with Augmented Reality (FARWAR).…”
Section: / 16supporting
confidence: 71%
See 1 more Smart Citation
“…The main finding had to do with the didactic potential to the learning experience by integrating AR and its development by the students. Finally, the work of Sanusi et al (2018) carried out through mobile devices and focusing in the learning of content for the class History of Architecture, confirmed the findings of other research that used AR in the classroom and concluded that its use with mobile devices benefited the flexible and intuitive learning of the students. Lastly, Villota and Vasconez (2020) conducted first-hand experimentation when they develop an AR app for first aid training named First Aid with Augmented Reality (FARWAR).…”
Section: / 16supporting
confidence: 71%
“…In regards to the hypothesis, H1 (There are significant differences depending on the macro-area of work origin) was studied in terms of dimension 1 which included its use in the classroom, its socio-educational vision, its use in inclusive areas and relationships, and as an element that enhances linguistic competence. H1 must be accepted as it was verified with the answers provided by the SE teachers from the areas of Engineering and Architecture (De la Torre et al, 2013;Sanusi et al, 2018) and those of Social and Legal Sciences (Márquez-Díaz & Morales-Espino, 2020). For dimension 2, it must also be accepted, since the representativeness in the areas of Engineering and Architecture, Social and Legal Sciences and Health Sciences, considered that it will enhance a critical vision of both the educational and social sphere in students compared to the areas that do not considered it.…”
Section: Discussionmentioning
confidence: 75%
“…Architecture is explored as a current practice in relation to architectural history and to the wider context of interaction between people and environment (Conway and Roenisch, 2005). Meanwhile, in the school of architecture, architectural history has been the core of the curriculum to understand the essence of architecture and relationship between humans and environment and to link knowledge acquisition with design practice (Sanusi et al. , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Architecture is explored as a current practice in relation to architectural history and to the wider context of interaction between people and environment (Conway and Roenisch, 2005). Meanwhile, in the school of architecture, architectural history has been the core of the curriculum to understand the essence of architecture and relationship between humans and environment and to link knowledge acquisition with design practice (Sanusi et al, 2018). Conway and Roenisch (2005) described the role of historical architecture as providing insight to the complexity and multicity of architecture, offering an explanation to account for architectural change, and defined architecture as follows: "Architecture is not only about the material environment, for buildings express our aspirations, our hopes for the future and our beliefs.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, computers and mobile phone devices can be used to create AR materials for education. Sanusi, Abdullah, Kassim and Tidjani (2018) assert that mobile augmented reality applications have gained popularity among architectural history education students in the education field. Klopfer and Squire (2008) aptly defined AR as "a situation in which a real world context is dynamically overlaid with coherent location or context sensitive virtual information" (p.205).…”
Section: Introductionmentioning
confidence: 99%